Image potential states at chevron-shaped graphene nanoribbons /Au(111) interfaces - Bronner, Christopher; Haase, Anton; Tegeder, Petra (Physical review. B, Condensed matter and materials physics, 2015)
Image potential states (IPSs) have been observed for various adsorbed carbon structures, such as graphene or carbon nanotubes. Graphene nanoribbons (GNRs) are intriguing nanostructures with a significant band gap which promise applications in nanotechnology. In the present paper we employ two-photon photoemission (2PPE) to investigate the unoccupied electronic structure and particularly the IPS of chevron-shaped GNR which are synthesized in a thermally activated on-surface synthesis on Au(111). Angle- and time-resolved 2PPE are utilized to gain further insights into the properties of the IPS. Compared to the pristine surface, reduced effective masses between 0.6 and 0.8 electron masses are observed and the lifetimes of the IPS are below the experimental detection limit, which is in the femtosecond regime. Independent of the concentration of N dopant atoms introduced in the GNR we observe a constant binding energy with respect to the vacuum level of the system.
Gesehen am 29.05.2020